2012
DOI: 10.1002/ajp.22065
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Networks for Ethologically Relevant Behaviors in Primates

Abstract: Parietal–frontal networks in primate brains are central to mediating actions. Physiological and anatomical investigations have shown that the parietal–frontal network is consistently organized across several branches of primate evolution that include prosimian galagos, New World owl and squirrel monkeys, and Old World macaque monkeys. Electrical stimulation with 0.5-sec trains of pulses delivered via microelectrodes evoked ethologically relevant actions from both posterior parietal cortex (PPC) and frontal mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
55
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 51 publications
3
55
1
Order By: Relevance
“…Finally, in apparent contrast with previous observations in monkey (2)(3)(4), in the present study, we did not identify complex neural representations for other ethologically relevant behaviors (e.g., defensive, manipulative) besides hand/mouth synergies. This could be taken as an indication that such representations do not exist in the human PrG, at least in the region we stimulated, but this hypothesis is unlikely.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Finally, in apparent contrast with previous observations in monkey (2)(3)(4), in the present study, we did not identify complex neural representations for other ethologically relevant behaviors (e.g., defensive, manipulative) besides hand/mouth synergies. This could be taken as an indication that such representations do not exist in the human PrG, at least in the region we stimulated, but this hypothesis is unlikely.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the generality of this model was recently challenged in nonhuman primates, where reaching, grasping, defensive, and hand/mouth movements have been found to be represented as complex motor primitives in independent circumscribed territories of the precentral gyrus (PrG) (2)(3)(4). To account for this observation, it was suggested that complex motor primitives have emerged during primate evolution to optimize the production of ethologically relevant behaviors (4). However, to date, direct evidence is lacking that such integrated representations of ethologically relevant movements also exist in humans.…”
mentioning
confidence: 99%
“…Second, the effect we report was regionally localized to a set of frontal regions and the thalamus, as opposed to the global effect reported in [49]. This last distinction is very important, because the richness of anatomical connectivity varies throughout the brain, from the regular structure of the cerebellum and primary cortices to the highly complex, variable and phylogenetically advanced frontal and parietal associative cortices [50,51]. Indeed, we observed that the functional exploration of frontothalamic anatomical connectivity was hindered under propofol, highlighting its importance for the maintenance of conscious awareness.…”
Section: Discussionmentioning
confidence: 72%
“…Reaching to grasp is a fundamental, ethologically relevant primate behavior (Kaas et al, 2013). Several cortical and subcortical structures are involved in the generation of these movements (Fattori et al, 2004;Grafton, 2010;Kaas et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Several cortical and subcortical structures are involved in the generation of these movements (Fattori et al, 2004;Grafton, 2010;Kaas et al, 2013). Recently, much emphasis has been placed on understanding the behavior of single cells in primary motor cortex (MI), one of the main sources of cortical output to the spinal cord during reach-tograsp movements (Saleh et al, 2010, Mollazadeh et al, 2011.…”
Section: Introductionmentioning
confidence: 99%